Mengelola Pikiran Negatif dengan Teknik Self-Talk, Teknik Reframing dan Thought Stopping - Siti Lutfiah; Qoqom Komariah; Ilham Adzikri; Imalatul Khairat (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Negative thinking represents a type of cognitive distortion that can negatively impact an individual's mental health and impede their ability to adapt effectively in daily life. This study aims to explore the effectiveness of three cognitive strategies self-talk, reframing, and thought stopping in managing such negative thoughts. Utilizing a qualitative research approach, this study conducted a literature review alongside participatory observation. Data were gathered by analyzing various academic articles, books, and journals focusing on these three techniques in the context of controlling negative thought patterns. Findings reveal that each technique offers unique benefits: self-talk helps in cultivating a more positive internal dialogue, reframing enables individuals to interpret problems from a more constructive angle, and thought stopping effectively halts the recurrence of negative thoughts through conscious intervention. These results indicate that these cognitive techniques can serve as practical psychological interventions for managing negative thinking.